Oviposition Preference of Pea Weevil, Bruchus pisorum L. Among Host and Non-host Plants and its Implication for Pest Management - Mendesil, Esayas; Rämert, Birgitta; Marttila, Salla; Hillbur, Ylva; Anderson, Peter (Frontiers in Plant Science, 2016)
The pea weevil, Bruchus pisorum L. is a major insect pest of field pea, Pisum sativum L. worldwide and current control practices mainly depend on the use of chemical insecticides that can cause adverse effects on environment and human health. Insecticides are also unaffordable by many small-scale farmers in developing countries, which highlights the need for investigating plant resistance traits and to develop alternative pest management strategies. The aim of this study was to determine oviposition preference of pea weevil among P. sativum genotypes with different level of resistance (Adet, 32410-1 and 235899-1) and the non-host leguminous plants wild pea (Pisum fulvum Sibth. et Sm.) and grass pea (Lathyrus sativus L.), in no-choice and dual-choice tests. Pod thickness and micromorphological traits of the pods were also examined. In the no-choice tests significantly more eggs were laid on the susceptible genotype Adet than on the other genotypes. Very few eggs were laid on P. fulvum and L. sativus. In the dual-choice experiments Adet was preferred by the females for oviposition. Furthermore, combinations of Adet with either 235899-1 or non-host plants significantly reduced the total number of eggs laid by the weevil in the dual-choice tests. Female pea weevils were also found to discriminate between host and non-host plants during oviposition. The neoplasm (Np) formation on 235899-1 pods was negatively correlated with oviposition by pea weevil. Pod wall thickness and trichomes might have influenced oviposition preference of the weevils. These results on oviposition behavior the weevils can be used in developing alternative pest management strategies such as trap cropping using highly attractive genotype and intercropping with the non-host plants.